Notas para un glosario sobre sillerías de oro. Las fuentes documentales leonesas - Teijeira Pablos, María Dolores (Estudios humanísticos. Geografía, historia y arte, 2001)
This article has been made in order to establish a Castilian terminology about choir stalls, not existing nowadays, using the same words that appear in the original documents.